Antibiotic treatment of Lyme borreliosis - Strle, Franc (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2001)
Treatment with antibiotics is indicated in all stages of Lyme borreliosis and for all clinical manifestations. It has been, however, most effective in the early course of illness. The choice of antibiotic depends on many factors, including the efficacy, pharmacokinetics, side effects, expected compliance, and price. For the majority of manifestations, the most effective antibiotic, the optimal dodage, and the most appropriate duration have not been exactly determined.Basic principles of antibiotic therapy of Lyme borreliosis and recommendations for treatment of this disease as used in Slovenia are presented.
Keywords: Antibiotics; Antibiotiki; Drug therapy; Lyme borelioza; Lyme disease; Lymska bolezen sin Lymska borelioza; zdravljenje